Harm and governance of prisons’ systemic overcrowding - Simone Santorso (Oñati Socio-Legal Series, 2025)
Overcrowding has been on the national policy agendas of many jurisdictions for decades. While many other aspects of punishment are largely investigated as penal policy-related issues, overcrowding has not received the same attention. This article investigates how we may best understand prison congestion by considering it as a widely accepted operational condition for many prison systems. Following a brief introduction on how overcrowding is a structural problem in many jurisdictions, the essay is developed into three independent, but related, parts: an analysis of overcrowding and its definitional issues that includes a discussion of the theoretical and epistemological challenges it poses; a discussion of the impact and legitimacy of congestion on incarceration experience via the notion of ‘harm’; and, finally, the discussion of the concept of ‘governance of systemic overcrowding’. By doing so the paper aims to challenge the current knowledge on prison overcrowding and wants to suggest a new analytical standpoint, which, however, is deserving of further research.